Instruction-Tuned 7B Models Outperform Base in Few-Shot Battery Anomaly Classification - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: Can instruction-tuned variants of 7B parameter models outperform base models in few-shot classification of battery management system anomalies without fine-tuning. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.3/10. This report is a machine-generated literature sy
Machine-generated literature synthesis.